A dual-mode system based on molybdophosphoric heteropoly acid and fluorescent microspheres for the reliable and ultrasensitive detection of alkaline phosphatase. Issue 6 (13th February 2023) - Li, Qiannan; Wang, Yufei; Zhu, Qianqian; Liu, Haifang; Liu, Jianbo; Meng, Hong-Min; Li, Zhaohui
Abstract : A novel colorimetric and fluorescent dual-mode sensing system based on molybdophosphoric heteropoly acid (PMA) and fluorescent microspheres (FMs) was established for monitoring the activity of alkaline phosphatase (ALP). Abstract : A novel colorimetric and fluorescent dual-mode sensing system based on molybdophosphoric heteropoly acid (PMA) and fluorescent microspheres (FMs) was established for monitoring the activity of alkaline phosphatase (ALP). In the presence of ALP, l -ascorbic acid-2-phosphate (AAP) could be hydrolyzed catalytically to ascorbic acid (AA), which could reduce PMA to phosphorus molybdenum blue (PMB), accompanied by the generation of colorimetric signals depending on the level of ALP. Meanwhile, the fluorescence of FMs was quenched markedly by the PMB produced due to the inner-filter effect, which constituted the response mechanism for the dual-mode sensing systems of ALP. On this basis, a PMA-FMs based dual-mode sensing system was used for the detection of ALP, which not only possessed remarkable sensitivity, with a limit of detection of 0.27 U L −1 and 0.11 U L −1, but also exhibited good analytical performance in biological samples with satisfactory results. Moreover, a simple and portable test kit for the visual detection of ALP in real serum samples was fabricated utilizing a smartphone with image-recognition and data-processing capabilities as a visual-detection platform.